THE OVEJERO MAGALLANICO DOG: GENOMIC ARCHITECTURE, INTERBREED RELATIONSHIPS AND GENE MUTATION TRACKING USING NEXT GENERATION SEQUENCING - Gómez - Jaramillo; Marcelo (2023)
RESULTADOS OBTENIDOS: Describa los resultados obtenidos de su investigación haciendo referencia a los objetivos originales y/o previamente modificados de su propuesta. La extensión máxima de esta sección es de 5 páginas (letra tamaño 10, Arial o Verdana). General Goal. To characterize the genomic arquitecture of the Ovejero Magallanico in the context of related breeds and search for the MDR1 gene mutation as a consequence of their historical relationship with the Collies lineage. Phylogenetic relationship among dog breeds To identify the relationship between PGODs and other recognized breeds, we generated a cladogram with SNPs from 1673 individuals representing 176 dog breeds, including PGOD, and two wild canids [4]. The cladogram was created using an identity by state (IBS) distance matrix and Neighbor Joining (NJ) phylogeny. On a consensus tree built with 100 bootstrap replicates, the PGOD clustered with the UK rural clade, one of the 23 groups identified by Parker et al. (2017), and specifically with the herding dog breeds with origins in the United Kingdom with a score of 92%. This genomic relationship mirrors historical records of the importation of PGOD from the UK and characteristics shared with the herding breeds [21]. From the 16 breed members of the UK rural clade, PGOD are on one branch that also includes the Border Collie and the Kelpie (Fig 2A). In addition, we found a geographic pattern in the phylogeny such that most PGODs from Northern Patagonia (the Aysén region in Chile, including seven dogs from the cross-border region of Chubut, Argentina) are more closely related to the Border Collie (100% bootstrap value), and PGODs collected in Southern Patagonia (Magallanes region in Chile) are closer to the Kelpie (100% bootstrap value) (Fig 1B). Fig 1. Phylogeny cladogram calculated by genetic distance. (A) Neighbor-Joining tree visualization of genetic distances, based on 100 bootstraps, and using SNP data from 176 breeds including Patagonian Sheepdog (PGOD) and 2 wild canids. Breeds are clustered if ...